Development and analysis of bread fortified with calcium extracted from chicken eggshells of Pakistani market - KHAN,Faima Atta (2021)
Abstract Calcium fortification is usually achieved by employing wheat flour as the most frequently used vehicle. In this study, potential of calcium extraction from chicken eggshell and its utilization as a bread fortificant in straight grade flour (SGF) is investigated. In addition, the fortified and unfortified (control) flour samples were evaluated for nutrient composition and rheological properties. Results showed that addition of fortificant at different concentrations significantly (p<0.05) enhanced calcium content of fortified flour and it was considerably increased from 115.80 mg/kg (To) to 1135.1 mg/kg (T3). Nutrient composition data of fortified flour have shown a significant (p<0.05) reduction in moisture content of flour from 12.7% (To) to 11.76% (T3) and protein content from 9.89% (To) to 9.79% (T3). However, a significant increase in ash content was observed by increasing fortificant level from 0.54% (To) to 1.04% (T3). Rheological properties indicated a significant increase in water absorption from 63.60 to 67.527%, dough development time (DDT) from 7.38 to 11.37 min and dough stability from 13.79 to 17.37 min. Textural characteristics of fortified bread revealed a significant reduction for hardness values from 11.40 N (control) to 6.50 N (T3) in response to fortificant addition. Quality assessment of bread indicated that bread quality was significantly affected with corresponding rises in fortificant addition levels.